Виокремлення середнього класу (за даними компанії TNS) - Сальнікова, Світлана Анатоліївна; Сальникова, Светлана Анатольевна; Salnikova, Svitlana A.; Хомяк, Андрій Олександрович; Хомяк, Андрей Александрович; Khomiak, Andrii O. (My University, 2016)
Задля виокремлення середнього класу на основі перетину множин, де множиною є конкретний критерій ідентифікації (відповідно, кількість таких множин залежить від кількості критеріїв), елементами множини – лише ті, які задовольняють задану умову, автори емпірично обґрунтували використання таких критеріїв його ідентифікації, як дохід, матеріальне становище, професійний статус. Установлення критичних значень для кожного критерію дало змогу, за даними компанії TNS, виокремити тих, хто має шанс потрапити до середнього класу. Зокрема, за критерієм доходу таких 35,6 %, роду занять – 37,0 %, матеріального становища – 60,7 %. Перетин відповідних множин виявив 11,9 % належних до середнього класу серед дорослого 16+ населення міст України (понад 50 тис.). Порівняння соціально-демографічних структур, належних до середнього класу (11,9 %) та неналежних до нього (88,1 %), засвідчило статистично значущі відмінності за віковою, освітньою, поселенською структурами, а також за сферою виробничої діяльності. Серединний прошарок є більш відчутним серед людей із вищою освітою та у великих містах України, його представники зайняті переважно у сфері економіки (торгівля, обслуговування, виробництво), освіти, науки й культури. In order to selection of the “middle class” based on the intersection of sets (each set is a specific criteria for the identification of the middle class (the number of sets depends on the number of criteria), and elements of the set are only those that satisfy the specified condition), the authors empirically set the validity of use of the following identification criteria: income, financial conditions, professional status (occupations). According to the empirical data from TNS, identified critical values for each criterion made it possible to distinguish those who have a chance to get into the middle class and who do not. In particular, by the criterion of income there is 35,6 % the inhabitants of towns / cities with chance to belong to the middle-class, by occupations – 37,0 %, by financial conditions – 60,7 %. The intersection of respective sets showed 11,9 % of those who belong to the middle class among the population 16+ in towns and cities of Ukraine (with populations over 50 thousand.). The comparisons of socio-demographic structures those who are belonged to the middle class (11.9 %) and who are not (88,1 %) demonstrate statistically significant differences in age, education, settlement structures, and also - in the sphere of industrial activity. «Middle layer» is more appreciable among people with high education and in major cities of Ukraine; its representatives are engaged mainly in the economy (trade, services, manufacturing), education, science and culture. The authors also consider that the volume of the first age group («16–34» – 4,4 %, «35–54» – 6,5 %, «55–65» – 1,0 %) is low because among the youngest group are most of those who have not yet realized their chances by the determined criteria (income, financial conditions, occupation). In particular, 8,2 % of students don’t have an opportunity to belong to the middle class (they didn’t get into the set of «occupation»).
Selection of Middle Class (According to the Empirical Data From TNS)
Keywords: вимірювання; суб’єктивні критерії ідентифікації середнього класу; перетин множин; відбір за умовою; структура середнього класу; measurement; subjective identification criteria of middle class; intersection of sets; selection by condition; the structure of middle class